Massive mortality of the giant freshwater mussel Anodontites trapesialis (Lamarck, 1819) (Bivalvia: Mycetopodidae) during a severe drought in a Neotropical reservoir - Paschoal,Lucas R. P. (2020)
In 2012, a severe drought struck the southeastern of Brazil compromising the Paraná River Basin reservoirs. Here, we described how this climatic event promoted a massive mortality of the giant freshwater mussel Anodontites trapesialis in Furnas reservoir and reported the consequences of this phenomenon. In November 2012, three quarters of 100 m2 were sampled in this reservoir, where 812 dead shells of A. trapesialis were analyzed and measured (33˫ 133 mm). The species showed an aggregated distribution with high density (X _ : 1.0 - 5.5 ind/m2). Despite the massive mortality detected in fi eld, it was possible to fi nd living specimens in a small channel in the studied area, allowing the species to survive the water level fl uctuations. Large adult individuals (100˫ 124 mm) were more affected by drought than juveniles, accounting for about 90% of the dead mussels analyzed. Two years after the massive mortality event, water level was not reestablished and a terrestrial succession (with elevations in the concentration of organic matter and calcium in sediment) was observed in the studied area. We verifi ed that the damming associated with extreme climatic events affect negatively the populations of A. trapesialis and should be faced as a conservationist problem.